Regulating Microvascular Free Flaps Reconstruction in “Schobinger Stage 4” Arteriovenous Malformations of Face - Balakrishnan, Thalaivirithan Margabandu; Ilayakumar, P.; Vijay, Bhattiprolu; Christabel, Prethee Martina; Prakash, Divya; Elancheralathan, K.; Narayanan, Sritharan; Janardhanam, Jaganmohan (Indian Journal of Plastic Surgery, 2023)
Objectives Arteriovenous malformations (AVMs) are high-flow, aggressive lesions that cause systemic effects and may pose a risk to life. These lesions are difficult to treat as they have a tendency to recur aggressively after excision or embolization. So, it requires a regulating free flap with robust vascular flow averting the postexcisional ischemia-induced collateralization, parasitization, and recruitment of neovessels from the surrounding mesenchyme—a phenomenon precipitating and perpetuating the recurrence of AVM.Materials and Methods Sixteen patients (12 males and 4 females) with AVMs Schobinger type 4 involving face were treated from March 2015 to March 2021 with various free flaps: three free rectus abdominis flaps, one free radial forearm flap, and twelve free anterolateral thigh flaps were used for reconstruction following the wide local excision of Schobinger type 4 facial AVM. The records of these patients were analyzed retrospectively. The average follow-up period was 18.5 months. The functional and aesthetic outcomes were analyzed with institutional assessment scores.Results The average size of the flap harvested was 113.43 cm2. Fourteen patients (87.5%) had good-to-excellent score (p = 0.035) with institutional aesthetic and functional assessment system. The remaining two patients (12.5%) had only fair results. There was no recurrence (0%) in the free flap group versus 64% recurrence in the pedicled flap and skin grafting groups (p = 0.035).Conclusion Free flaps with their robust and homogenized blood supply provide a good avenue for void filling and an excellent regulating effect in inhibiting any locoregional recurrences of AVMs
Keywords: facial arteriovenous malformations; microvascular reconstruction; regulating free flaps